Impact of mandatory masking amid the COVID-19 pandemic on outdoor smoking: an interrupted time-series analysis of a 33-month unobtrusive observational study - Sun, Yuying; Wu, Yongda Socrates; Cheung, Yee Tak Derek; Wang, Man Ping; Chen, Jianjiu; Leung, Lok Tung; Zhang, Xiaoyu; Chak, Kin Yeung; Lam, Tai Hing; Ho, Sai Yin (Frontiers in Public Health, 2023)
Background: Mask-wearing in outdoor public places in Hong Kong was mandated on 29 July 2020 amid the COVID-19 pandemic. We aimed to evaluate the impact of mandatory masking with no exemption for smoking on outdoor smoking. Methods: We conducted 253 unobtrusive observations at ten outdoor smoking hotspots in 33 months from July 2019 to March 2022 and counted smokers and non-smoking pedestrians in fixed boundaries. We conducted interrupted time-series analyses on the monthly mean volume of smokers (persons per hour) using generalised linear models. The independent variables were time since the first observation, implementation of the mask regulation, time since the regulation, seasonality, wave 1-2, wave 3, wave four and wave five outbreaks. We checked the robustness of the association using the daily mean volume of smokers as the dependent variable. Two sensitivity analyses were conducted to include hotspot location or the number of all pedestrians as an offset. Results: Monthly outdoor smoking decreased immediately after the regulation (incidence rate ratio [IRR]: 0.505, 95% confidence interval [CI]: 0.374 to 0.680, P<.001). Daily smoking analysis and the two sensitivity analyses supported the results. However, monthly outdoor smoking increased by 11% since the regulation (IRR: 1.110, 95% CI: 1.074 to 1.147, P<.001). An exception was observed at the most severe wave five outbreak when monthly outdoor smoking decreased (IRR: 0.415, 95% CI: 0.327 to 0.525, P<.001). Conclusion: Outdoor smoking fell immediately after mandatory masking, rebounded to pre-pandemic levels and decreased again at the most severe wave 5.